Studi Perilaku Bullying Pada Siswa Sekolah Menengah Atas: Pendekatan Regresi Logistik Biner - Humalanggi, Ghita Juliana; Nurwan; Payu, Muhammad Rezky Friesta (Griya Journal of Mathematics Education and Application, 2025)
Bullying is a social problem that has a negative impact on students' psychological development and learning environment. This study aims to develop a binary logistic regression model to explain bullying behavior and the factors that significantly influence bullying behavior among students at SMA Negeri 1 Tibawa. The method used was a quantitative survey through a questionnaire with 54 statements, including the variable bullying behavior (Y) and five independent variables: individual factors (X1), family factors (X2), peer factors (X3), school factors (X4), and social media factors (X5). A sample size of 300 students was selected using simple random sampling technique from a population of 1,197 students. The analysis was conducted using binary logistic regression with the help of RStudio software. Partial test results show that only peer factors (X3) have a significant effect on bullying behavior. The odds ratio value shows that students with moderate and high levels of peer influence are 7.47 and 38.34 times more likely to engage in bullying behavior compared to low levels. The Hosmer-Lemeshow test showed the model fit the data. In conclusion, the binary logistic regression model can explain bullying behavior, with peer factors as the dominant factor that needs to be the focus of prevention in the school environment.